Меридионально ориентированные погребения Приднепровской Лесостепи скифского времени - Бойко, Ю. Н. (Давнина. Харківський історико-археологічний щорічник, 2016)
SUMMARY Boyko U.N. Meridian-Oriented Burials of the Pridnieper Forest-steppe of Scythian Times The article considers the detale analysis of Dniper’s Woodensteppe north-south orientated scythien time barrows. It yields a conclusion about Boudioi-Boudinoi origine of this kind of graves, one of iranian tribes, mentioned by Herodotus in Media and Wooden-steppe Scythia.